2020
DOI: 10.11622/smedj.2019118
|View full text |Cite
|
Sign up to set email alerts
|

Survey of neuromuscular monitoring and assessment of postoperative residual neuromuscular block in a postoperative anaesthetic care unit

Abstract: Online first papers have undergone full scientific review and copyediting, but have not been typeset or proofread. To cite this article, use the DOIs number provided. Mandatory typesetting and proofreading will commence with regular print and online publication of the online first papers of the SMJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…However, a study in a teaching hospital in Singapore found that the majority of anaesthetists (98.7%) did not routinely use PNS monitoring, and that PNS monitoring was only used in 17.9% of patients. 4 The prevalence of PRNB detected in the post anaesthetic care unit was 33.4%. Factors associated with this include a lack of knowledge and education on neuromuscular monitoring.…”
Section: Dear Editormentioning
confidence: 92%
See 2 more Smart Citations
“…However, a study in a teaching hospital in Singapore found that the majority of anaesthetists (98.7%) did not routinely use PNS monitoring, and that PNS monitoring was only used in 17.9% of patients. 4 The prevalence of PRNB detected in the post anaesthetic care unit was 33.4%. Factors associated with this include a lack of knowledge and education on neuromuscular monitoring.…”
Section: Dear Editormentioning
confidence: 92%
“…Factors associated with this include a lack of knowledge and education on neuromuscular monitoring. 4 The study's survey questionnaire revealed an underestimation of PRNB and incorrect answers by up to 69% of respondents, including those for the definition of PRNB, and the timing and use of reversal agents. 4 Our recommendations aim to promote appropriate use of neuromuscular blockade and its monitoring, and so improve the safety of anaesthesia care in Singapore.…”
Section: Dear Editormentioning
confidence: 95%
See 1 more Smart Citation
“…5 However, although it has been over 20 years since experts first recommended routine use of quantitative monitoring, 6 many anesthesiologists do not routinely use quantitative monitoring, which provides real-time TOFR measurements. [7][8][9][10][11] Sugammadex is a highly efficacious agent for reversal of rocuronium-and vecuronium-induced neuromuscular blockade; most hospitals currently have sugammadex on their formularies, but some clinicians are restricted from its routine use due to concerns for higher cost. [10][11][12][13] There is no broad consensus on the role for sugammadex, whether it should be used routinely or only selectively.…”
Section: Glossarymentioning
confidence: 99%
“…Many places still perform procedures without monitoring. 6,7 It is a basic safety feature that should be regarded as essential as oxygen saturation or heart rate measurement. and emotional intelligence' 1 and for acknowledging the importance of occupational wellbeing of anaesthesiologists.…”
mentioning
confidence: 99%